EFEKTIVITAS PELAKSANAAN PERATURAN MENTERI KESEHATAN NOMOR 290 TAHUN 2008 TENTANG PERSETUJUAN TINDAKAN KEDOKTERAN DI FASILITAS PELAYANAN KESEHATAN RUMAH SAKIT GIGI DAN MULUT UNIVERSITAS JENDERAL SOEDIRMAN PURWOKERTO - riska nurfadilah; dwi hapsari retnaningrum; kuat puji prayitno (Jurnal Idea Hukum, 2021)
Approval of medical measures is approval given to the patient or the patient'sfamily after getting complete information about the medical action to be done and therisks. According to Decree No. 290 of 2008, all medical measures must be approved.Lawsuits and lawsuits against doctors and hospitals in Indonesia today often occur, oneof which is related to medical records. Based on this background, the author formulatedthe problem of how effective the implementation of medical action approval based onDecree No. 290 of 2008 at Rsgm Unsoed Purwokerto and whether the factors that affectthe effectiveness of the implementation of medical action approval based on Decree.This research is an empirical juridical type of research, which examines legalprovisions derived from secondary data in the form of primary, secondary, and tertiarylegal materials and from primary data obtained from respondents and sources byconducting research in the field in the form of observations and interviews then analyzedqualitatively and the results of analysis are explained by descriptive methods. Thelocation of the study is at purwokerto Dental and Oral Hospital.Based on the results of the analysis, it was concluded that the implementation ofmedical approval at RSGM Unsoed has not been fully effective. Factors that affect theimplementation of approval of medical actions based on Decree No. 290 of 2008 at RsgmUnsoed Purwokerto are factors of legal substance, legal structure and legal culture ofrsgm unsoed community. The substance factor of the law is the director's regulationwhich still does not fully refer to Permenkes 290 of 2008. The legal structure hasconstraints on law enforcement related to the limited number of human-age resourcesthat result in the absence of supervision of the implementation of approval of medical anddentist actions that are not professionalism. Legal cultural factors have constraints in theform of low patient legal awareness, lack of patient knowledge levels, and indifference topatients. Another factor that affects is the infrastructure factor. Suggestions for RSGMUnsoed, among others, need to be made policies related to supervision and enforcementof the implementation of medical action approvals and must be socialized, policies needto be made in the integration unit, the addition of dentists and provide leaflets to takehome related to medical actions that will be carried out by dentists